The complete chloroplast genome sequence of medicinal plant: Cynanchum thesioides (Asclepiadaceae) - Peng Kang; Yuqian Guo; Yiyue Zhang; Yuqing Wei (Mitochondrial DNA. Part B. Resources, 2021)
Cynanchum thesioides is a medicinal plant. The complete chloroplast genome sequence of is 158,547 bp in length, contains 131 complete genes, including 85 protein-coding genes (85 PCGs), 8 ribosomal RNA genes (8 rRNAs), and 37 tRNA genes (37 tRNAs). The overall AT content of cp DNA is 62.1%, the corresponding values of the LSC, SSC, and IR regions are 63.7, 67.7, and 56.5%. Phylogenetic tree shows that C. thesioides was identified as the most divergent among the sequenced species of Cynanchum used.